Georg Friedrich Händel's strokes - Bäzner, Hansjörg; Hennerici, Michael G. (Cerebrovascular diseases, 2004)
Georg Friedrich Händel was a musical giant and probably the first composer to be the manager and promoter of his own works. The story of his life and illnesses is full of myths, invented and embellished by various biographies. Existing pathographies written by authors from various specialities suggested he suffered from psychiatric diseases like cyclothymia or mania and rheumatologic disorders like arthritis, while others tended to interpret his recurrent palsies as typical sequelae of ischemic strokes. During the last years of life, Händel was struck with blindness, which in his era was interpreted as being due to cataracts. This led to three 'coucher' operations, all of them without lasting effect. Although a definite diagnosis cannot be inferred from the original sources, the most plausible explanation for Händel's palsies and visual impairment may be cerebrovascular disease. The possible differential diagnosis will be discussed in this paper.
Gesehen am 11.05.2022